LANGUAGE RIGHTS AND GLOBALIZATION: LEGAL FRAMEWORKS AND THEIR EFFECTIVENESS - Alikberova Kamila Adhamovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the intersection of language rights and globalization, focusing on the legal frameworks that protect linguistic diversity and their effectiveness in a rapidly globalizing world. As globalization promotes the dominance of certain languages, it poses challenges to the preservation of minority languages and the rights of speakers. This study employs a qualitative analysis of international and national legal instruments, supplemented by case studies from various regions. The findings reveal that while legal frameworks exist to protect language rights, their implementation varies significantly, often influenced by political, social, and economic factors. The article concludes with recommendations for enhancing the effectiveness of language rights protections in the context of globalization.